Microstructures and Mechanical Properties of As Cast (Al7.5Co21.9Cr10.9Ti5.0Fe21.9Ni32.8)100-xCux High-Entropy Alloys - Li, Jiajun; Dong, Yu; Wang, Zemin; Liu, Min; Ding, Yi; Fu, Bin; Wang, Zhanyong (Frontiers in Materials, 2021)
This study focused on the role of Cu in the microstructure characteristics and tensile properties of novel L12-strengthened multicomponent high-entropy alloys (HEAs). A series of as-cast (Al7.5Co21.9Cr10.9Ti5.0Fe21.9Ni32.8)100-xCux (x=0.5, 2.5, 5.0) high-entropy alloys (HEAs) were prepared. The microstructures and mechanical properties of HEAs were investigated using X-ray diffraction, a scanning electron microscope, a transmission electron microscope, and atom probe tomography. The XRD patterns of HEAs confirmed that all HEAs consisted of the FCC phase and the L12 phase. As Cu content increased, the dendritic was gradually coarsened. The spherical L12 size decreased, and number density increased in the dendritic regions (DR). The L12 mainly contained Ni, Ti, Al, and Cu. The acicular L12 size increased and was continuously distributed in the interdendritic regions (ID) as the Cu content increased gradually. The ultimate strength and elongation decreased from 1002 MPa, 20.0% to 906 MPa, 13.1%, respectively. The segregation rates of Ti, Cu, and Al increased in the DR and ID. The L12 nano-precipitates in the DR become denser and finer, while the L12 islets in the ID region increase and elongate. Large lattice distortion caused by Cu addition weakens the strength of the L12-FCC phase boundary, leading to the premature fracture of the three HEAs, which were the main reasons for the decreases in strength and ductility as Cu content increased.